The Effects of TIG Welding Rod Compositions on Microstructural and Mechanical Properties of Dissimilar AISI 304L and 420 Stainless Steel Welds - Aziz Barış Başyiğit (Metals, 2018)
The usage of AISI/SAE 304L austenitic and 420 martensitic stainless steels is receiving greater interest especially in the defence and navy industries. 304L stainless steels exhibit excellent resistance to oxidizing media, while martensitic 420 alloy provides high strength values besides satisfactory corrosion properties at ambient atmospheres. In this work; 420 quality martensitic stainless steel is TIG (Tungsten Inert Gas) welded with 304L quality low carbon austenitic stainless steel plates. As filler metal dominantly determines the weld metals chemical compositions and final microstructures, 3 different TIG welding rods of ER312, ER316L ve ER2209 are used in welding operations in order to obtain 3 discrete weld metal contents under high purity argon shielding gas. Microstructural inspection, microhardness survey and Charpy V-notch impact tests are applied to all joints after welding operations. The specimen welded by ER2209 TIG welding rod executed the highest impact test results besides exhibiting the lowest micro-hardness profiles at heat affected zones and weld metals. All of the welded specimens weld region hardness profiles were determined to be lower than unwelded 420 martensitic stainless steel base metal.